Aesthetics of structural formation in European Renaissance sculpture - Khalid Akram Mohammed Alobadi, Prof. Rana Hussein Hatef (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The research was concerned with the aesthetics of structural formation in the European Renaissance sculpture, the research contained the research problem, the importance of the research and the need for it, the goal of the research by knowing the aesthetics of structural formation in the European Renaissance sculpture, while the limits of the research were determined by studying (the aesthetics of structural formation in Renaissance sculptures European) and implemented with a variety of materials, and completed within the period (1406-1497 AD), and then specifying and defining the search terms. It included the theoretical framework and previous studies, and it contained a study on the aesthetics of structural formation in the Renaissance sculpture, and contained the research procedures that included a community, a sample, the research method and the research tool, and then analyzing the samples that amounted to (3) samples. It included the research results and conclusions, as well as recommendations and suggestions. Among the most prominent findings of the research: The plastic treatments of the sculptural building represent the artist’s aesthetic style and a sensory way to show the beauty of previous ideas of the sculptural work, as in the statue of Moses by the sculptor Klaus Slaughter in the sample model No. (1). The artist of the Renaissance moved away from literal forms and naive transportation when his beauty centered on the essential form of man and nature, as favorite subjects through which the artist presented an improved image of reality full of transcendence, majesty and beauty, as in the statue of David by the sculptor Donatello in sample model No. (2). Among the conclusions reached by the researcher are the following: One of the most important things to note is that most of the sculptural works in the European Renaissance have themes that include religious or noble figures, and therefore the sculptural structural formation appears, which combines all the elements of sensual beauty to appear in the form of an integrated human beauty to an extent Big. Artists of the Renaissance set out with thoughtful structural formations governed by ideal aesthetic laws. Where the artist of the Renaissance moved away from literal forms and naive transmission when his beauty centered on the essential form of man and nature, as favorite subjects through whom the artist presented an improved image of reality full of sublimity, majesty and beauty, according to the concepts of classical tendency. While the research ended with some recommendations and suggestions, and then proved the sources, references and supplements.